Eksplorasi kepedulian, tanggung jawab, dan sikap lingkungan terhadap konsumsi hijau Generasi Y-Z - Theresia Vania Raditya; Yasintha Soelasih (Jurnal Manajemen Maranatha, 2025)
Environmental issues arising from plastic waste, particularly single-use plastic bottles, highlight the urgency of adopting more sustainable consumption practices. This study aims to examine the influence of environmental concern, environmental responsibility, and environmental attitude on green consumption behavior, focusing on the use of tumblers as an alternative to single-use plastic bottles. In addition, this research analyzes the moderating role of generational characteristics, specifically Generations Y and Z, in these relationships. The study employed a non-probability sampling method with purposive sampling, selecting participants based on characteristics considered most relevant to the research objectives. A total of 135 respondents aged 13-44 years with prior experience using tumblers participated in the survey. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that environmental responsibility has a positive and significant effect on green consumption behavior, as does environmental attitude. Meanwhile, environmental concern also exerts a positive influence, but its effect varies across generations. The generational moderation analysis indicates that Generation Z demonstrates stronger environmental concern, while Generation Y shows greater consistency in translating moral responsibility and environmental attitude into green consumption practices. The implications of this study provide practical insights for the development of environmental campaigns and marketing strategies that are more effective in encouraging the adoption of eco-friendly products among younger generations.